Analysis on the impact of foreign exchange differences on the financial performance of Malaysia public listed companies / Lee Seng Fatt and Kweh Qian Long - Fatt, Lee Seng; Long, Kweh Qian (2012)
The management of a company cannot afford to leave the profits generated from its operation to be eroded by any unforeseen currency turmoil. If unprotected, the company may face drastic cost escalation on account of higher exchange rates for imported components during a currency crisis. In this respect, multinational companies traditionally rely on the expertise of its treasury department to manage its exchange risk exposure through undertaking various hedging measures against their forward foreign exchange commitments and export receipts. This study aimed to identify the relationship between foreign exchange differences and financial performance of public-listed companies in Malaysia as well as to determine the existence of any protection measure taken against foreign exchange risk.